Enhancement of Thermal Tolerance and Growth Performances of Asian Seabass (Lates calcarifer) Fed with Grape Extract Supplemented Feed - Akram, Salman; Ranasinghe, Naveen; Lee, Tsung-Han; Chou, Chi-Chung (Animals (Basel), 2024)
Cold snaps during the winter present a critical challenge for Asian seabass (Lates calcarifer) in Taiwan, as sudden temperature drops significantly affect their growth and survival. This study explores the effects of dietary grape extract (GE) from Vitis vinifera on the growth performance, oxidative stress regulation, and thermal tolerance of this commercially valuable fish. Over a 60-day feeding trial, four dietary groups were tested: a control diet without GE and three diets supplemented with GE at 2% (GE20), 3% (GE30), and 4% (GE40) with commercial feed. The results demonstrated that GE supplementation positively influenced growth, with the GE20 group achieving the best weight gain and feed conversion ratio among all groups. The upregulation of the growth-related gene igf-1 in the liver of the GE20 group further supported its superior growth performance. Additionally, GE-fed groups showed increased expression of antioxidant-related genes sod1 and sod2 in the liver, while gpx1 exhibited a significant increase only in the GE20 group, indicating enhanced antioxidant defenses. Cat gene expression remained unchanged, and higher GE doses reduced the expression of gpx1, cat, and igf-1. Furthermore, GE supplementation improved cold tolerance in all treated groups compared to the control. These findings suggest that dietary GE at 20 g/kg is particularly effective in enhancing growth performance and cold tolerance in Asian seabass, offering a promising strategy for boosting fish health and adaptability in aquaculture.